Back View of Beauty: A Bias in Attractiveness Judgment. (January 2013) - Yonemura, Keiichi; Ono, Fuminori; Watanabe, Katsumi
Attractiveness judgment based on visual appearance seems easy and almost automatic. However, it becomes difficult when we need to rely on glances of a person's back view (eg while passing on the street). How is attractiveness judgment from the back view consistent with that from full-front view? In experiment 1 participants rated the attractiveness of human heads photographed from behind and from the front. Attractiveness ratings between the back and front views were weakly but significantly correlated. However, on average, the back-view photographs were rated more attractive than the front-view photographs. The tendency was most conspicuous when the male participants viewed the photographs of women. In experiment 2 participants were explicitly asked to predict the facial attractiveness of each head's front view based on the back view. Again, the predicted attractiveness based on the back view was higher than the actual rating of the front-view photographs, and the difference reached significance when the male participants viewed the women photographs. These biases in attractiveness judgment would be related to attractiveness judgments in everyday situations where straight full-frontal encounters are rare.